Tax Evasion through Trade Intermediation : Evidence from Chinese Exporters - Liu, Xuepeng; Shi, Huimin; Ferrantino, Michael (World Bank, Washington, DC, 2015)
Many production firms use intermediary trading firms to export indirectly. This paper uses Chinese export data at the transaction level to investigate the tax evasion motive through indirect trade. The paper provides strong evidence that, under Chinas partial export value-added tax rebate policy, production firms can effectively evade value-added taxes by underreporting their selling prices to domestic intermediary trading firms, especially when they sell differentiated products. Even for a moderate level of underreporting, the revenue loss is close to one billion U.S. dollars. The paper also finds that such underreporting behavior through domestic intermediaries may be associated with cross-border evasion through underreporting export values to foreign partners. In addition, the results indicate that the evasion motive is stronger for larger transactions.